Treatment of Tumour in Horseshoe Kidney: A Retrospective Study - Dr. Sanjay P. Dhangar (SP’z Series New Insights on Urology and Urological Research Part I, 2022)
Introduction: Horseshoe kidney is a developmental disorder of genitourinary system and is a renal fusion anomaly. This condition is itself rare in its occurrence. The occurrence of tumour in a horseshoe kidney is further rare. The isthmus has the most tumours, followed by the right and left sides. It is more frequent in men, with a 2:1 ratio. The best treatment for a tumour in a horseshoe kidney is surgical removal. At our institute, we’ve dealt with a tumour in the horseshoe kidney, and we’d want to explain what we’ve discovered. Materials and Methods: The procedure was performed in Nashik, Maharashtra, India, at the SMBT Institute of Medical Sciences and Research Center. This study covered all patients diagnosed with a tumour in the horseshoe kidneys and later operated on between August 2016 and July 2019. The study involved three patients in total. Ultrasonography (USG), computed tomography (CT) urography, and CT angiography were used to make the preoperative diagnosis. Following the surgery, USG, CT, and X-rays of the chest were used to conduct follow-up examinations at 1, 3, and 6 months. In all of the cases, a radical nephrectomy or heminephrectomy was performed. Results: The study involved three patients in total. Two of them were men and one was a woman. One patient’s first symptom was haematuria. One patient’s first symptom was abdominal pain, and another patient was diagnosed with a tumour in the horseshoe kidney by chance. One patient had a tumour in the right half of the kidney, another had a tumour in the left half of the kidney, and a third had a tumour in the isthmus extending into the right kidney. One patient had a tumour in the upper pole, while the other two had tumours in the lower pole. The tumours ranged in size from 10 cm to 6 cm in diameter. Heminephrectomy was performed in two patients by lumbar posterolateral incisions, while one patient underwent a midline incision since the tumour was located in the isthmus and extended to the right side of the body. All of the patients were found to be clear of metastases during follow-up exams. Conclusion: The most prevalent malignant tumour in the horseshoe kidney is RCC. When surgical intervention is contemplated, a CT angiography should be performed to obtain an accurate view of the renal vasculature, particularly the isthmus. Depending on the size and location of the tumour, organ preservation surgery may be performed. Surgery can be performed openly, laparoscopically, or robotically.